Refleksi atas beberapa isu kebijakan pendidikan - Sukarno, Makmuri (Jurnal Kependudukan Indonesia, 2007)
Although SBY-JK’s government has been sharper in responding to the demand for basic education, nevertherless, the utilization of school/madrasah’s autonomy for accumulating money from the community as an input, mostly in secondary level, was lacking in accountability and public political participation and tending to exacerbate social gap in education. Therefore, issues on output, public accountability and widening the chance of those who have not enough financial supports are becoming great challenges in the future. Accordingly, government’s policy on these issues need to be delivered through an adequate system.